Ludwig Wittgenstein: Language and Culture - Nwobu, Emmanuel Nnamdi (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2019)
This work focuses on the relation between language and culture from the perspective of Wittgenstein’s philosophy. The focus is not on how the meanings of words and sentences of a language is dependent on the culture of the language users; but how an understanding of the notions of meaning and language can be a basis of an understanding of culture. To do this I will start by discussing why the study of language and its meaning is so vital in philosophy for Wittgenstein. This will require the understanding of Wittgenstein’s ideas on language and meaning. I will outline Wittgenstein’s philosophy of language and meaning. Then, a discussion on the connection of this conception of language and meaning with culture will follow. I will conclude this work by giving the nature and meaning of culture which can be derived from the understanding of Wittgenstein’s philosophy of language.